2010
DOI: 10.36076/ppj.2010/13/e343
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-Induced Urologic Insult (KIUI)

Abstract: K etamine initially introduced as an anesthetic agent in the 1960s, is a receptor complex antagonist n-methyl-d-aspartic acid that has been used as an anesthetic and/or analgesic for many years. In the past decade the use of ketamine as an analgesic or "analgesic adjuvant" appears to have increased. Subanesthetic doses of ketamine have been utilized for analgesia and opioid-sparing effects in chronic pain as well as in refractory cancer pain, and palliative medicine (1-11). Additionally, recently its use studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…The dysregulation of purinergic neurotransmission may underlie the detrusor overactivity in this animal model [ 18 ]. A denuded epithelium, chronic inflammation, ulcerative cystitis, and erythematous necrotic cystitis are frequently found in ketamine cystitis bladders [ 19 ]. Another study reported that ketamine enhanced the generation of oxidative stress mediated by mitochondria- and endothelial reticulum-dependent pathways.…”
Section: P Athophysiologymentioning
confidence: 99%
“…The dysregulation of purinergic neurotransmission may underlie the detrusor overactivity in this animal model [ 18 ]. A denuded epithelium, chronic inflammation, ulcerative cystitis, and erythematous necrotic cystitis are frequently found in ketamine cystitis bladders [ 19 ]. Another study reported that ketamine enhanced the generation of oxidative stress mediated by mitochondria- and endothelial reticulum-dependent pathways.…”
Section: P Athophysiologymentioning
confidence: 99%
“…Η κεταμίνη είναι ουροτοξική (επαγόμενη από κεταμίνη ουροτοξικότητα (Ketamine-induced urological toxicity, KIUT) σε περιπτώσεις βαριάς χρήσης κεταμίνης κι ένα ποσοστό 20-30% των ατόμων που κάνουν συχνή χρήση της αναφέρει αιτιάσεις σχετιζόμενες με την ουροδόχο κύστη. 26,46 Η κατάχρηση λοιπόν της κεταμίνης κι όχι η χορήγησή της σε θεραπευτικό πλαίσιο προκαλεί τοξικά αποτελέσματα στο εσωτερικό επιθήλιο της ουροδόχου κύστεως, που είναι γνωστό και ως ουροθήλιο 47 αλλά και σε λοιπά όργανα του ουροποιητικού συστήματος. Ορισμένοι ωστόσο συγγραφείς υποστηρίζουν πως η KIUT μπορεί να παρατηρηθεί και σε υπο-αναισθητικές δόσεις κεταμίνης (0,5-1,0 mg/kg).…”
Section: δυνητική τοξικότητα για το ουροθήλιο και το ήπαρunclassified